RELATIONSHIP BETWEEN WARM ISCHEMIC TIME AND RESISTIVE INDEX ON CREATININ REDUCTION RATIO DAY TWO AFTER LIVING KIDNEY DONOR TRANSPLANTATION - Lusito; Ayudyah Nurani; Dwi Lestari Partiningrum; Arwedi Arwanto; Lestariningsih; Shofa Chasani (Midwifery Department of Sultan Agung Islamic University of Semarang, 2022)
Kidney transplantation (KT) may improve kidney function, via filtration, excretion, and hormonal function better than other kidney replacement therapies. Many factors may cause graft rejection or delayed graft function which may decrease the prognosis for graft survival. This study aims to determine associated factors of serum creatinine reduction ratio day 2 (CRR2) after living kidney donor transplants. This research used a retrospective cohort study design, with total sampling based on complete documents was done. A total 44 respondents (from 2012 to January 2020) and 22 respondents (based on the complete Resistive Index (RI) were recorded since 2018). Early Graft Function was defined using CRR2. Immediate Graft Function (IGF) was defined if CRR2 > 30% and Delayed Graft Function (DGF) if CRR2 ≤ 30%. The results of Multiple logistic regression analysis from 44 samples showed that Warm Ischemic Time (WIT) ≤ 40 minutes was significantly associated with IGF (OR 10.78; 95%CI: 1.66 to 70.16; p=0.01). A result with 22 samples showed that, only RI ≤ 0.7was significantly associated with IGF (OR 0.11; 95%CI: 0.03-0.41; p=0.002). In conclusion, WIT and RI influence on EGF with parameters CRR2 of living-donors. KT Patients with WIT ≤40 minutes and RI ≤0.7 had a higher risk of IGF.